Cross-faculty proximity and academic entrepreneurship: The role of business schools - Maximilian Goethner; Michael Wyrwich (Friedrich Schiller University Jena, 2017)
Over the past decades, entrepreneurial activity has started to be considered a third mission of higher education institutions. Our study examines the extent to which entrepreneurship at universities is driven by spatial proximity between university faculties. To this end, we use a new dataset that links information on business idea generation by faculties of German universities between 2007 and 2014 with comprehensive data on structural characteristics of these universities and faculties (e.g., number of academic staff, students, industry funding). Our analysis shows that the emergence of entrepreneurial ideas in natural sciences is positively affected by proximity to business schools. This pattern suggests the presence of knowledge flows between university faculties as an important source of science-based and technology-oriented business ideas.
Keywords: D24; L26; M13; O31; O32; 330; Academic entrepreneurship; Knowledge Spillover; Spatial Proximity; Entrepreneurial Human Capital